The Effect of Radiation on Properties of Polymers - McKeen, Laurence W., author 519968; ScienceDirect (Online service) 7722 (Kidlington : William Andrew, 2020)
The Effect of Radiation on Properties of Polymers examines the effects of radiation on plastics and elastomers. Polymers are required in products or parts for a range of cutting-edge applications that are exposed to radiation, in areas such as space, medicine, and radiation processing. This book focuses on the effects of radiation exposure within that environment, providing in-depth data coverage organized by category of polymer. Aspects such as radiation impact on mechanical and thermal properties, including glass transition and heat deflection temperatures, are described, demonstrating how changes in these properties affect the performance of plastic or elastomer parts. The effect of radiation on electrical properties is also included. Supporting introductory chapters explain the key concepts of radiation, including the physical, mechanical, and thermal properties of plastics and elastomers. This is a vital resource for plastics engineers, product designers, and R&D professionals, working on products or parts for radioactive environments, as well as engineers and scientists in the medical, nuclear, and radiation processing industries. The book also supports researchers and scientists in plastics engineering, polymer processing and properties, polymer and coatings chemistry, materials science, and radiation.